2020
DOI: 10.1108/lm-02-2020-0032
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory survey measuring burnout among academic librarians in the southeast of the United States

Abstract: PurposeThe main purpose of this work is to uncover and identify the issues that academic librarians consider important in the attainment of work–life balance. This work will focus on exploring their experiences with different dimensions of burnout.Design/methodology/approachThe topic of burnout is explored by analyzing the results of a survey based on the Maslach Burnout Inventory (MBI), which was distributed among librarians at a group academic institutions that are members of the Association of Southeastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Their survey indicated that 70% of US academic librarians are sometimes, often, or always burned out; and almost 50% are experiencing work-related burnout (Wood et al, 2020). Although Colon-Aguirre and Webb (2020) did not find evidence of overall burnout within their sample population of academic librarians in the Southeast US, they did find higher levels of job exhaustion and cynicism, which are contributors to overall burnout in younger librarians and those who were unmarried or without children. This potential risk of burnout and the factors that may contribute to it could also be a future research topic.…”
Section: Discussion/conclusionmentioning
confidence: 90%
“…Their survey indicated that 70% of US academic librarians are sometimes, often, or always burned out; and almost 50% are experiencing work-related burnout (Wood et al, 2020). Although Colon-Aguirre and Webb (2020) did not find evidence of overall burnout within their sample population of academic librarians in the Southeast US, they did find higher levels of job exhaustion and cynicism, which are contributors to overall burnout in younger librarians and those who were unmarried or without children. This potential risk of burnout and the factors that may contribute to it could also be a future research topic.…”
Section: Discussion/conclusionmentioning
confidence: 90%
“…Researchers have identified triggering events and behaviors, such as workplace abuse by managers and administrators, as potential causes for low morale and burnout among librarians. Relatively little data has been collected in this area thus far, with the largest and only quantitative study by Colon-Aguirre and Webb (2020) garnering 525 full responses.…”
Section: Work and The Academic Library Professionmentioning
confidence: 99%
“…Job satisfaction, morale, and burnout among librarians and library workers have become favored topics among library and information science researchers (Colon‐Aguirre & Webb, 2020; Falcone & McCartin, 2022; Kendrick, 2017; Kendrick & Damasco, 2019; Martin, 2020). The recent surge in such studies reflects broader societal concerns about social justice and institutional accountability, especially in the US academy (Lopez, 2021; Rothman & Barraza Mendoza, 2021; Wilder, 2013).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Colon-Aguirre and Webb's analysis includes all roles in academic libraries, including technical services, but they did not find that technical services staff were impacted by burnout in a significant way. 25 Although research has been steadily published on the overall burnout trends in libraries, causes of burnout, recognizing burnout, etc., few studies have followed through on how to mitigate and prevent burnout. Qualitative studies sharing experiences, ideas, and opinions on how to prevent and mitigate burnout in libraries are much more common than quantitative approaches.…”
Section: Literature Reviewmentioning
confidence: 99%